Developing a Decision Support System of Land Location for Apartment Investment Using Fuzzy MADM Yager Model - Honggowibowo, Anton Setiawan (Sekolah Tinggi Teknologi Adisutjipto, 2018)
Determining the location of land for apartment investment is usually done manually by relying on intuition, experience, and some considerations from the apartment developer. For this reason, the determination of the location of the land must go through the right analysis and calculation so that the best location can be determined from various criteria. Fuzzy Multiple Attribute Decision Making (FMADM) method Yager model is a decision support system method that can be used in this system. This FMADM method will compare alternative locations with predetermined criteria including land prices, land area, road access, land conditions, and the environment. The final result of this process is the selection of total values to obtain alternative locations, so that the best results from three alternative locations are obtained, namely Banguntapan with the largest total value of 0.600, Seturan with values of 0.085, and Kulon Progo with a value of 0.292. So the location of Banguntapan can be used as a recommendation for the developer in making a decision to determine the location of the land for apartment investment